2022
DOI: 10.1097/jcma.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension in the elderly population

Abstract: Pulmonary arterial hypertension (PAH) was a disease predominantly affecting young females about 40 years ago; however, it has been increasingly diagnosed in elderly individuals. Few studies have investigated the features of elderly patients with PAH. This review provides an overview of the characteristics of elderly patients with PAH compared to young patients. The examination of the changing demographics of the population with PAH revealed that the mean age has increased over the years. In addition, the inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Surprisingly, a previous study reported that BNP or NT-proBNP had a 98% sensitivity for excluding high right atrial pressure (≥ 8 mmHg) and low cardiac index (< 2.5 L/min/m 2 ), and in circumstances of extreme low BNP (< 50 pg/mL) or NT-proBNP (< 300 pg/mL) level, hemodynamic measurements no longer had independent prognostic predictive values [ 14 ]. Moreover, COMPERA and the SPAHR registries demonstrated that the ability of mortality prediction is excellent even when only about a third of patients are followed up under the assessment of right heart catheterization [ 15 , 18 ]. Nevertheless, due to the complexity of pulmonary hypertension, any single biomarker is insufficient for the broad assessment of patients with different etiologies of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a previous study reported that BNP or NT-proBNP had a 98% sensitivity for excluding high right atrial pressure (≥ 8 mmHg) and low cardiac index (< 2.5 L/min/m 2 ), and in circumstances of extreme low BNP (< 50 pg/mL) or NT-proBNP (< 300 pg/mL) level, hemodynamic measurements no longer had independent prognostic predictive values [ 14 ]. Moreover, COMPERA and the SPAHR registries demonstrated that the ability of mortality prediction is excellent even when only about a third of patients are followed up under the assessment of right heart catheterization [ 15 , 18 ]. Nevertheless, due to the complexity of pulmonary hypertension, any single biomarker is insufficient for the broad assessment of patients with different etiologies of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Many registries have been established to assess the characteristics of patients suffering from PH since 1980s. They demonstrated an increasing trend in the mean age of PH patients over the past forty years [ 3 ]. In the first registry of PH conducted by the National Institute of Health in the United States between 1981 and 1985, only 9% of patients were >60 years of age with a mean age of 36 years [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 Dr. Wang’s current study used “60” years of age as cutoff value, many studies used “65” as watershed. 10,11…”
mentioning
confidence: 99%
“…It is well-known that the elder population is associated with worse prognosis in almost all diseases, 9 even though it is not consistent to define what is the appropriate cutoff value for elder age. 8,10,11 Dr. Wang's current study used "60" years of age as cutoff value, many studies used "65" as watershed. 10,11 Second, it is relatively difficult to identify who have an impaired bone marrow function.…”
mentioning
confidence: 99%
See 1 more Smart Citation